Vastus lateralis represents the association between neuromuscular activation and thermoregulation in cycling - Priego, J. I.; Carpes, F. P.; Bini, R. R.; Salvador, R.; Pérez Soriano, P.; Cibrián, R. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction Fitness level improves the efficiency of the thermoregulatory system. However, it is still unknown how neuromuscular activation affects skin temperature. Therefore, this study assessed the relationship between neuromuscular activation and skin temperature during cycling exercise. Methods: Ten male physically active participants underwent an incremental cycling test to exhaustion while muscle activation was recorded from rectus femoris (RF), vastus lateralis (VL), biceps femoris (BF) and gastrocnemius medialis (GM). Muscle recruitment was assessed via frequency band analyses of muscle activation signals. Thermography images were recorded before and immediately after exercise at four body regions of interest corresponding to the muscles where EMG activity was recorded. Results: Significant inverse relationship between variation in skin temperature and variation in overall neuromuscular activation (p<0.04,r>0.5) and significant positive relationship between skin temperature and low frequency components of neuromuscular activation (p<0.01,r>0.7) were observed for vastus lateralis. Discussion: A recent study (Abate et al. 2013) showed differences in thermoregulation due to level of physical fitness. Higher maximum overall activation is associated with better fitness level (Häkkinen et al. 1998) and our participants used large motor units rather than small (less low frequency component) to sustain the increases in workload (Gregory and Bickel 2005). For this reason, larger increases in skin temperature for participants presenting increased low frequencies and limited overall activation of vastus lateralis during maximal aerobic exercise could be associated to their reduced fitness level. In conclusion, participants with higher overall muscular activation and lower frequency content in activation for vastus lateralis presented a better adaptive response of their thermoregulatory system by showing limited increases in skin temperature. Vastus lateralis seems to be the muscle that better illustrate relationships between skin temperature and muscle activation